Ethnicity, Economy, and Violence: The 1997 Tragedy in the Narrative of the Chinese Ethnic Group in Makassar - Ansar, Mutakharah; Auliah, Fidya; Purnamasari, Fitra Dwi; Alfaziri, Amri; Kabubu, Rusmala Dewi (Universitas Negeri Makassar, 2025)
The conflict between the Chinese and indigenous communities in Makassar in 1997 represented a tragedy that reflected long-standing socio-economic and political tensions. This study aims to explore the causes, dynamics, and impacts of the conflict from the perspective of the Chinese community, as well as to seek reconciliation solutions to foster inter-ethnic harmony. Employing a descriptive qualitative method with a historical approach, the research collects data through in-depth interviews with affected members of the Chinese community, complemented by analysis of various written sources. The findings indicate that the conflict was initially triggered by an individual incident that escalated into mass violence, driven by economic inequality, negative stereotypes, and discriminatory policies during the New Order regime. From the Chinese community’s perspective, the conflict reflects a lack of justice and legal protection, underscoring the need for concrete measures to overcome intergroup prejudice. The event caused not only material losses but also deep psychological trauma for the Chinese community. Reconciliation efforts through cross-cultural dialogue, respect for diversity, and social justice are seen as crucial in preventing similar future conflicts. This research contributes to a deeper understanding of inter-ethnic dynamics in Indonesia and supports the application of multicultural values to strengthen national unity.